Serum C-peptide, IGFBP-1 and IGFBP-2 and risk of colon and rectal cancers in the European Prospective Investigation into Cancer and Nutrition. - Jenab, M; Riboli, E; Cleveland, R; Norat, T; Rinaldi, S; Nieters, A; Biessy, C; Tjønneland, A; Olsen, A; Overvad, K; Grønbaek, H; Clavel-Chapelon, F; et al. (2007)
Western style diets and lifestyles are associated with increasing rates of obesity, diabetes and insulin resistance. Higher circulating insulin levels may modulate cell proliferation and apoptosis either directly or indirectly by increasing the bioactivity of IGF-I and decreasing the bioactivity of some of its binding proteins. The objective of this study was to determine the association of increasing levels of serum C-peptide, a biomarker of pancreatic insulin secretion, and IGF binding proteins (IGFBP) -1 and -2 with colorectal cancer risk in a case-control study nested within the European Prospective Investigation into Cancer and Nutrition (EPIC), a large cohort involving 10 Western European countries. A total of 1,078 colorectal cancer cases were matched (age, date of blood donation, fasting status, gender, study center) to an equal number of control subjects. Relative cancer risks were estimated using conditional logistic regression models. Serum C-peptide concentration was positively associated with an increased colorectal cancer risk for the highest versus the lowest quintile (OR=1.56, 95% CI=1.16-2.09, p(trend)<0.01), which was slightly attenuated after adjustment for BMI and physical activity (OR=1.37, 95% CI=1.00-1.88, p(trend)=0.10). When stratified by anatomical site, the cancer risk was stronger in the colon (OR=1.67, 95% CI=1.14-2.46, p(trend)<0.01) than in the rectum (OR=1.42, 95% CI=0.90-2.25, p(trend)=0.35). The cancer risk estimates were not heterogeneous by gender or fasting status. No clear colorectal cancer risk associations were observed for IGFBP-1 or -2. This large prospective study confirms that hyperinsulinemia, as determined by C-peptide levels, is associated with an increased colorectal cancer risk.